AN ANALYSIS OF POLITENESS STRATEGY IN MATA NAJWA “ONDE MANDE PARLEMEN” EPISODE - Adi Sutrisno; Guntur Agus Permana (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
This research purposed to find the types of politeness strategy and to describes, explain the impacts of politeness strategy that used in Mata Najwa “Onde Mande Parlemen” episode based on politeness theory by Brown & Levinson. This research was used a descriptive qualitative, the primary source of the data is utterance that included of politeness strategy in Mata Najwa “Onde Mande Parlemen” episode. The secondary source of this research is all of information it can be collected from newspaper, comments on social media, article etc that related with this object. The data collection method used in this research is observation method by Sudaryanto. The research found the types of politeness strategy amounting to 88 data divided into: positive strategy 57 data, negative strategy 21 data, bald off record strategy 10 data. The sample of analysis will be starting in positive strategy, negative strategy and the last bald off record strategy.